The Safety and Efficacy of Pregabalin Add-on Therapy in Restless Legs Syndrome Patients - Bae, Hyoeun; Cho, Yong Won; Kim, Keun Tae; Allen, Richard P.; Earley, Christopher J. (Frontiers in Neurology, 2021)
Pregabalin is increasingly being used as a first-line treatment for symptomatic control of restless legs syndrome (RLS). This study aimed to evaluate the efficacy and safety of pregabalin as an add-on therapy in RLS patients already taking dopamine agonists (DA) but still in need of further management. Patients with idiopathic RLS were enrolled, and all had already been prescribed DA for at least three months but still had either persistent symptoms, side effects or comorbid insomnia. An initial dose of 75mg pregabalin was begun, adjusted as needed, and maintained at a stable dose for 4 weeks, followed by observation for a total of 8 weeks. RLS symptoms and insomnia scores were evaluated before and after add-on pregabalin treatment. Patients were monitored for side-effects that could be attributed to pregabalin. A total of 32 RLS patients were enrolled, and 20 subjects remained until the endpoint. After pregabalin add-on, mean IRLS score showed significant improvement compared to the baseline (p<0.001). The insomnia severity index score also improved (p=0.036), and no serious adverse effects were observed. Our preliminary data suggests the potential for pregabalin as an add-on therapy to DA with regards to both efficacy and safety in patients who have inadequate RLS improvement.